Plasmatic Levels of IL-18, IP-10, and Activated CD8+ T Cells Are Potential Biomarkers to Identify HIV-1 Elite Controllers With a True Functional Cure Profile - Côrtes, Fernanda H.; de Paula, Hury H. S.; Bello, Gonzalo; Ribeiro-Alves, Marcelo; de Azevedo, Suwellen S. D.; Caetano, Diogo G.; Teixeira, Sylvia L. M.; Hoagland, Brenda; Grinsztejn, Beatriz; Veloso, Valdilea G.; Guimarães, Monick L.; Morgado, Mariza G. (Frontiers in Immunology, 2018)
Elite controllers (ECs) are rare individuals able to naturally control HIV-1 replication below the detection limit of viral load (VL) commercial assays. It is unclear, however, whether ECs might be considered a natural model of a functional cure because some studies have noted CD4+ T cell depletion and disease progression associated with abnormally high levels of immune activation and/or inflammation in this group. Here, we propose the use of immunological parameters to identify HIV-1 ECs that could represent the best model of a functional cure. We compared plasma levels of six inflammatory biomarkers (IP-10, IL-18, sCD163, sCD14, CRP, and IL-6) and percentages of activated CD8+ T cells (CD38+HLA-DR+) between 15 ECs (eight with persistent undetectable viremia [persistent elite controllers-PECs] and seven with occasional viral blips [ebbing elite controllers-EECs]), 13 viremic controllers (VCs - plasma viral load between 51-2,000 RNA copies/ml), and 18 HIV-1 infected patients in combined antiretroviral therapy (cART), with suppressed viremia and 18 HIV-uninfected controls (HIV-neg). The two groups of ECs presented inflammation and activation profiles similar to HIV-neg individuals, and there was no evidence of CD4+ T cell decline over time. VCs, by contrast, had higher levels of IL-18, IP-10 and CRP and a lower CD4/CD8 ratio than that of HIV-neg (P < 0.05). Plasma levels of IL-18 and IP-10 correlated positively with CD8+ T cell activation and negatively with both CD4/CD8 and CD4% in HIV-1 controllers. These results suggest that most ECs, defined using stringent criteria in relation to the cut-off level of viremia (≤ 50 copies/mL) and a minimum follow-up time of > 5 years, show no evidence of persistent inflammation or immune activation. This study further suggests that plasmatic levels of IL-18/IP-10 combined with the frequency of CD8+CD38+HLA-DR+ T cells can be important biomarkers to identify models of a functional cure among HIV-1 ECs.